A Case of Liver Injury Mimicking Metastasis After Gamma Knife Therapy for Lung Cancer: Evaluating by 18F-FDG PET/CT. (November 2018) - Tang, Kun; Zheng, Xiangwu; Lin, Jie; Yin, Weiwei
Abstract : Abstract: A 52-year-old man presented a mixed low-density lesion with high FDG uptake in hepatic segment VIII after gamma knife therapy for lung cancer, which was easily misdiagnosed as hepatic metastasis. Follow-up PET/CT assessment demonstrated that the hepatic lesion was barely observed and without FDG accumulation 5 months after radiotherapy. This case suggests that a new FDG-avid lesion at PET/CT after radiotherapy for lung cancer can be caused by radiation-induced liver injury. Knowledge of its imaging characteristics and nature course evaluated by follow-up PET/CT is critical to avoid misinterpretation of this lesion as metastases.